Pengembangan Media Kartu Kuartet Menggunakan Aplikasi Canva untuk Penambahan Pengetahuan Kosakata pada Siswa Kelas 1 SDN 101968 Petumbukan - Chairunisya, Ninda; Ramadhani, Mastari; Ramadhan, Nuri (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2024)
This study is motivated by the limited vocabulary acquisition among children, the lack of media variation in learning, and minimal student engagement in the learning process. The research aims to develop an effective quartet card media to enhance students' vocabulary at SDN 101968 Petumbukan. This study employs a research and development (R&D) approach based on the Borg & Gall model, following nine stages of development. The research subjects consist of 15 students. Data collection techniques include questionnaires and interviews, with research instruments comprising structured questionnaires and interview guidelines. The data were analyzed using a quantitative descriptive analysis with percentage calculations. The findings indicate that quartet cards are a viable instructional medium for improving elementary school students' vocabulary acquisition. This is supported by validation results from material experts, who rated the media as eligible (82.5%), media experts who classified it as highly viable (92%), initial field trials categorized as successful (86.9%), main field trials also classified as successful (88.0%), and operational field trials rated as successful (86.3%). The overall percentage from all trials reached 87.0%, indicating that the quartet card media is an effective tool for vocabulary development in elementary education.